Human Pegivirus infection and lymphoma risk and prognosis: a North American study. (29th May 2018) - Fama, Angelo; Xiang, Jinhua; Link, Brian K.; Allmer, Cristine; Klinzman, Donna; Feldman, Andrew L.; Nowakowski, Grzegorz S.; Liebow, Mark; Larson, Melissa C.; Maurer, Matthew J.; Ansell, Stephen M.; Novak, Anne J.; et al.
Summary: We evaluated the association of Human Pegivirus (HPgV) viraemia with risk of developing lymphoma, overall and by major subtypes. Because this virus has also been associated with better prognosis in the setting of co‐infection with human immunodeficiency virus, we further assessed the association of HPgV with prognosis. We used risk factor data and banked plasma samples from 2094 lymphoma cases newly diagnosed between 2002 and 2009 and 1572 frequency‐matched controls. Plasma samples were tested for HPgV RNA by reverse transcription polymerase chain reaction (RT‐PCR), and those with RNA concentrations <5000 genome equivalents/ml were confirmed using nested RT‐PCR methods. To assess the role of HPgV in lymphoma prognosis, we used 2948 cases from a cohort study of newly diagnosed lymphoma patients (included all cases from the case‐control study). There was a positive association of HPgV viraemia with risk of lymphoma overall (Odds ratio = 2·14; 95% confidence interval [CI] 1·63–2·80; P  <   0·0001), and for all major subtypes except Hodgkin lymphoma and chronic lymphocytic leukaemia/small lymphocytic lymphoma, and this was not confounded by other lymphoma risk factors. In contrast, there was no association of HPgV viraemia with event‐free survival (Hazard ratio [HR] = 1·00; 95% CI 0·85–1·18) or overall survival (HR = 0·97; 95% CI 0·79–1·20) for lymphoma overall, or any of the subtypes. These data support the hypothesis for a role of HPgV in the aetiology of multiple lymphoma subtypes.